Selected National Trends in Educational Administration - Alfred P. Wilson (Educational Considerations, 1973)
In the decade ahead, who will determine and teach the skills necessary for the administration of public education? What will be the future of school boards? These are two of the major questions this author sees as confronting teachers of educational administration if present trends continue.